Structure and Usage of the Vocal Repertoire of Callithrix jacchus - Bezerra, Bruna Martins; Souto, Antonio (International journal of primatology, 2008)
We recorded the vocal repertoire and behavior of individuals from 3 groups of wild common marmosets ( Callithrix jacchus ) via focal sampling and ad libitum sampling in a fragment of Atlantic Rain Forest in Pernambuco, northeast Brazil. Our aims were: 1) to provide a detailed quantitative description of the vocalizations and vocal repertoire of common marmosets in the wild, and to compare the repertoire with that described from conspecific captives; 2) to investigate if differences exist in vocal repertoire between wild individuals of different ages; and 3) to explore the behavioral contexts associated with specific vocalizations in free-living Callithrix jacchus . This is the first study describing common marmoset calls in the wild and it shows that their vocal repertoire comprises 13 different calls. Though wild and captive calls were similar, differences occurred in the form of the alarm calls given for different potential predators, the tsê call, and very brief whistle. In addition, the tsee call did not occur in wild individuals and wild infants did not utter the twitter call. The age of the subjects influenced the call types present in the vocal repertoire, e.g., the loud cry was specific to infants, whereas only adults gave alarm calls. The behavior of both the caller and the potential receivers seemed to affect the frequency of wild common marmoset calls. One could predict intricate vocalization-based communications for the system based on their relatively complex social organization and densely leafed arboreal habitat. Our study confirms the prediction.